OPTIMIZING BUSINESS PERFORMANCE IN PROPERTY MANAGEMENT WITH GREEN BUILDING EVIDENCE IN INDONESIA - David Kiki Baringin MT Samosir (Media Riset Akuntansi, Auditing & Informasi, 2022)
Indonesia has not widely implemented green buildings although such buildings offer many benefits to their occupants and property management firms. In this respect, this study seeks to test the effect of green buildings on business performance. This research expands GBCI’s green building indicators with an indicator of continuous and design process to operationalize the green building variable. Meanwhile, the measurement of business performance refers to the balanced scorecard for sustainability (BSCS) concept that adds the environmental perspective into the conventional BSC. Surveying 126 manager respondents representing 89 green and non-green buildings, the study finds that green building implementation positively affects business performance. Thus, our hypothesis is empirically supported.